EFFECT OF SALT STRESS ON THE IMBIBITION CURVE OF COWPEA SEEDS (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
The salinity of soil and water of irrigation can cause negative effects to agriculture by affecting the development and productivity of the cultivated species. These effects can be mitigated with the cultivation of salinity-tolerant varieties. The objective of this study was to evaluate the effect of salinity on the water imbibition curve during the germination process in cowpea seed and the response of different cultivars. An experiment was conducted in a factorial scheme, composed of three cultivars (BRS Marataoã, BRS Pajeu and BRS Tumucumaque) and four levels of salt stress, obtained by NaCl solutions at concentrations of 50, 100 and 150 mM and control, distilled water. The treatments were arranged in a completely randomized design, with four repetitions. The variables analyzed were the pattern of imbibition curve and final seed water content. It was found that the evaluated cultivars do not present the three-phase pattern for the seed soaking curve, in the absence or presence of salinity. There is variability for the pattern of the seed soaking curve among BRS Marataoã, BRS Pajeu and BRS Tumucumaque cowpea cultivars. Salinity acts by reducing the water content of cowpea seeds during the germination process and causes alteration in the pattern of the water soaking curve by the seeds. The cultivar BRS Tumucumaque shows higher tolerance to the reduction of seed water content under salt stress conditions when compared to the cultivars BRS Pajeu and BRS Marataoã.